Studies on Fungal Diseases of Eggplant in Relation to Statistical Analysis and Making of a Disease Calendar - Pandey, Adarsh (Recent Research in Science and Technology, 2010)
Brinjal is consumed enormously in India. Bareilly City is sandwiched between two rivers and has tarai climate. Therefore it is prime location of marketing neighboring cities. Bareilly is situated at foothills of Himalaya where generally the climate is moderate, humid and cloudy. Different atmospheric factors viz. T.max., T.min., Relative humidity and Rainfall play importantÂ role in development of fungal diseases on Brinjal. Five Fungi were encountered during the cropping year on Brinjal viz. Fusasium solani, Helminthosporium spiciferum, Choanephora cucurbitarum, Curvularia lunata, Trichothecium roseum. The growth of these fungi was found luxurious especially from October to November, and Feb. to April. Fruit spoilage was maximum from August to January; the reason may be high humidity, high temperature, and less rainfall.